PHP, MySQL, & JavaScript all-in-one for dummies - Blum, Richard, 1962- (--For dummies., 2018)
Explore the engine that drives the internet It takes a powerful suite of technologies to drive the most-visited websites in the world. PHP, mySQL, JavaScript, and other web-building languages serve as the foundation for application development and programming projects at all levels of the web. Dig into this all-in-one book to get a grasp on these in-demand skills, and figure out how to apply them to become a professional web builder. You'll get valuable information from seven handy books covering the pieces of web programming, HTML5 & CSS3, JavaScript, PHP, MySQL, creating object-oriented programs, and using PHP frameworks. Helps you grasp the technologies that power web applications Covers PHP version 7.2 Includes coverage of the latest updates in web development Perfect for developers to use to solve problems This book is ideal for the inexperienced programmer interested in adding these skills to their toolbox. New coders who've made it through an online course or boot camp will also find great value in how this book builds on what you already know.